Anthony & Cleopatra [Antónius a Kleopatra anglicky] - Shakespeare, William, 1564-1616 (A Shakespeare children's story, 2020)
"Anthony and Cleopatra" is a brilliant tragedy - drama of love and war by William Shakespeare. The play is set in ancient Rome and Egypt, and portrays actual events from Roman history. It revolves around its two main characters, Anthony, a Roman General, and Cleopatra, the Queen of Egypt. Anthony falls in love with Cleopatra, and throughout the play remains torn between his duty and his love for her.